STRATEGI IMPLEMENTASI PERCEPATAN PEMBERANTASAN KORUPSI - Drs. Awang Anwaruddin (Pusjar SKPP Lembaga Administrasi Negara, 2005)
Since the last two months, two extraordinary issues in home country have shaken the political world. Alas, both issues concerns the most-hated moral patoplogy: corruption! The first issue relates to the case of bribery by an eminent member of General Election Comission (KPU), and the second is the case of corruption indication by the Chief Director of Bank Mandiri. The new lesson of both cases is hopefully that our government has entered a new era of corruption abolition: enforcing law and order fairly to any citizens without considering their status. A condition that hardly happened during the previous governments! Such high spirit of abolishing corruption seems triggered by the President Yudoyono’s commitment to make 2005 as the Year of Corruption Abolition. The commitment was then strengthened by the launching of several steps on abolsihing corruption last month, following the Presidential Instruction Number No. 5/2004 on the Alleviation of Corruption Abolition.